Two-Dimensional N-Glycan Distribution Mapping of Hepatocellular Carcinoma Tissues by MALDI-Imaging Mass Spectrometry - Thomas W. Powers; Stephanie Holst; Manfred Wuhrer; Anand S. Mehta; Richard R. Drake (Biomolecules, 2015)
A new mass spectrometry imaging approach to simultaneously map the two-dimensional distribution of N-glycans in tissues has been recently developed. The method uses Matrix Assisted Laser Desorption Ionization Imaging Mass Spectrometry (MALDI-IMS) to spatially profile the location and distribution of multiple N-linked glycan species released by peptide N-glycosidase F in frozen or formalin-fixed tissues. Multiple formalin-fixed human hepatocellular carcinoma tissues were evaluated with this method, resulting in a panel of over 30 N-glycans detected. An ethylation reaction of extracted N-glycans released from adjacent slides was done to stabilize sialic acid containing glycans, and these structures were compared to N-glycans detected directly from tissue profiling. In addition, the distribution of singly fucosylated N-glycans detected in tumor tissue microarray cores were compared to the histochemistry staining pattern of a core fucose binding lectin. As this MALDI-IMS workflow has the potential to be applied to any formalin-fixed tissue block or tissue microarray, the advantages and limitations of the technique in context with other glycomic methods are also summarized.